2014
DOI: 10.1111/exd.12437
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: to treat or to manage?

Abstract: The recognition of psoriasis as a systemic disorder with characteristic skin symptoms and associated diseases has changed treatment concepts substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 64 publications
(59 reference statements)
0
78
0
4
Order By: Relevance
“…In fact, investigations have assessed the effect of weight-loss on psoriasis and conclusively found that the severity of psoriasis can be significantly improved. The most convincing data are derived from bariatric surgery where the majority of patients show a significant improvement of psoriasis severity [101] . However, there is no data yet available that demonstrates a lasting effect of weight loss measures on psoriasis severity/ activity after the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, investigations have assessed the effect of weight-loss on psoriasis and conclusively found that the severity of psoriasis can be significantly improved. The most convincing data are derived from bariatric surgery where the majority of patients show a significant improvement of psoriasis severity [101] . However, there is no data yet available that demonstrates a lasting effect of weight loss measures on psoriasis severity/ activity after the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…There is an agreement that mild psoriasis should preferentially be treated with topical therapy and, in case of inadequate response, UV-light should be added. In case of moderate-to-severe psoriasis systemic therapy should be initiated [101][102][103][104] . Methotrexate (MTX), cyclosporine A (CsA) and retinoids are common and efficacious systemic agent used for the treatment of moderate to severe psoriasis, but their long-term use is hindered by safety concerns and, in particular, by the risk of hepatotoxicity.…”
Section: Conventional Psoriatic Treatments and Liver Function Implicamentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was calculated based on web-site calculator [15] , taking the total size of Almadina Almonawara population (1180770) [16] , confidence level (95%) and margin error (5%) to be 385. Additional 20 % was added to cover the missing data.…”
Section: Method:-mentioning
confidence: 99%
“…Multidisciplinary and integrated approach to the disease has been targeted instead of treatment in disease management. This is reached by description of accompanying diseases and adaptation of treatment according to existing comorbidities [1][2][3][4]81 .…”
Section: Patient Evaluation/managementmentioning
confidence: 99%